DIALING AND INVESTIGATION OF NOTARY BY INVESTIGATOR POLICE - Nur Aisyah (UNISSULA, 2018)
Relationship notary to do with legal issues consciously or notary in practice are often faced with the proceedings or deal with the authorities caused the parties to a deed in front of him, and that the dispute can be reported to the investigator. So often a notary summoned by investigators with regard to the deed he made. In terms of the calling and notary investigation by an investigator there own rules set out in the Act. Although the implementation of the functions and investigations and inquiries Act gives the right to call, check, catching, defense minister, searched, confiscated to suspects and items are considered connected with a criminal offense, but in exercising its rights and authority must be obedient and subject to the principle of the right of due process (upholding the rights of the accused in the process of law enforcement). Each suspect is entitled researched and investigated based in accordance with the applicable law of criminal procedure. The concept of due process associated with the foundation of upholding the rule of law in dealing with crime. No one is located and put themselves above the law and the law should be applied to anyone based on the principle of treatment in an honest way. The application of the criminal law should be in accordance with the constitutional requirements and must comply with the law. By karen it does not allow the violation of a part of the general provisions on the pretext in order to enforce another law section.